PENINGKATAN KINERJA SUMBER DAYA MANUSIA MELALUI KECERDASAN SPIRITUAL DAN KEPEMIMPINAN TRANSFORMASIONAL DI FAKULTAS EKONOMI UNISSULA SEMARANG - Restu Restu; Wasitowati Wasitowati (Jurnal Ekonomi dan Bisnis, 2016)
ABSTRACTThis study is aimed to describe and analyze the relevance between spiritualism intelligence andtransformational leadership toward lecturer performance. The parameters were estimated byquestionnaire data, with 65 respondents had worked in Economic Faculty of UNISSULA. Linearregression models are developed to examined the hypothesis which used SPSS (StatisticalPackage for Social Sciences) 20 for windows. The dependent variable of this model is lecturerperformance, whereas the independent variable of this model is spiritual intelligence andtransformational leadership. The result of the data analysis by using SPSS (Statistical Packagefor Social Sciences) indicates: if the spiritual intelligence is increase, so lecturer performance isincrease too, if transformational leadership is increase, so lecturer performance is increase too.Keywords: Human Resource Performance, spiritual intelligence and transformationalleadership.